The Transformation of Religious Values in The Era of Digital Technological Development: a Critical Review of Islamic Digital Spirituality - Fadilah, Nurul; Oktarosada, Dwi; Hirzi, Muhammad Haikal (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This study aims to analyze the transformation of religious values in digital society, focusing on value reinterpretation, virtual religious practices, and the influence of social media on the young generation's spirituality. This literature review uses a qualitative approach, employing a literature review method, analyzing 15 reputable international journal articles indexed in Scopus and Web of Science from 2021-2024, and 2 international reference books. Data analysis employs an Integrative Review approach, including problem identification, literature search, quality evaluation, thematic analysis, and narrative synthesis. Results show that digital technology has transformed the religious paradigm from traditional collective practices toward more individual and flexible spiritual experiences. Digitalization opens wide access to religious teachings but poses challenges to authenticity and the depth of religious understanding. The religious mediatization phenomenon presents symbolization of religious practices that tend to emphasize visual aspects rather than teaching substance. This transformation creates duality between easy access to religious information and risks of meaning deviation and excessive individualization in religion. This study contributes to understanding how digital media reshape religious identity among young generations and provides theoretical and practical implications for developing religious education models relevant to the contemporary digital context.